The Portrayal of Liberal Feminism through the Main Character of Charlotte Bronte's Jane Eyre Novel - Sari, Lia Paramita; Lubis, Indah Sari; Ariani, Setya (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This research discusses about the portrayal of liberal feminism experienced by the main character in the Jane Eyre novel. In conducting this research, the researcher used the theory of liberal feminism and the theory of characterization by Reaske. The researcher used qualitative research as the method and mimetic as the approach of this research. The findings of this research showed that there are two aspects of liberal feminism that are portrayed in the novel; namely equal education and equal liberty. Those aspects are portrayed through Jane Eyre’s character when she struggled to get her freedom by being intelligent and progressive to get well education, and being independent and courageous to get her freedom.